Pelatihan Manajemen Database dan Website Bootstrap untuk Digitalisasi Administrasi Jemaat GKPS Maranatha - Elwin Yunith Purba; Andreas Jorghy Parapat; Saferius Harefa (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
Effective congregational data management and information dissemination have become essential components in supporting church administration and ministry in the digital era. However, many churches continue to encounter challenges in managing congregational databases and utilizing information technology, particularly in the development of web-based information systems. To address these challenges, a Community Service Program (PKM) entitled "Database Management Socialization for the GKPS Maranatha Congregation and Website Development Training Using Bootstrap for Church Council Members" was conducted. This program aimed to enhance participants' knowledge and practical skills in managing congregational data through database management concepts and to introduce website front-end development using the Bootstrap framework. The program was implemented through lectures, demonstrations, hands-on practice, discussions, and interactive question-and-answer sessions. The training materials included fundamental database management concepts, the importance of structured data management, an introduction to relational databases, and the application of Bootstrap for developing responsive and user-friendly web interfaces. The participants consisted of GKPS Maranatha congregation members and church council members responsible for administrative and ministerial activities. The results indicated a significant improvement in participants' understanding of systematic database management and their basic competencies in designing responsive website interfaces using Bootstrap. Furthermore, participants demonstrated a high level of enthusiasm and engagement throughout the program, as evidenced by their active involvement in practical exercises and discussions. This community service initiative is expected to encourage the sustainable adoption of information technology in church administration and support the development of effective, efficient, and sustainable web-based information services.